2015
DOI: 10.1039/c5dt00187k
|View full text |Cite
|
Sign up to set email alerts
|

In vitro selection of deoxyribozymes active with Cd2+ ions resulting in variants of DNAzyme 8–17

Abstract: In vitro selection was performed to search for RNA-cleaving DNAzymes catalytically active with Cd(2+) ions from the oligonucleotide combinatorial library with a 23-nucleotide random region. All the selected, catalytically active variants turned out to belong to the 8-17 type DNAzyme. Three DNAzymes were prepared in shortened, cis-acting versions which were subjected to a detailed study of the kinetic properties and metal ion preferences. Although the selection protocol was designed for Cd(2+)-dependent DNAzyme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
44
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(44 citation statements)
references
References 50 publications
(107 reference statements)
0
44
0
Order By: Relevance
“…Many interesting progresses were made by using transition metal ions 7, 11, 35. Many DNAzymes were reported to use Zn 2+ 26, 36, UO 2 2+ 14, Cu 2+ 37, Cd 2+ 29, 38, Hg 2+ 39, and Ag + 40. We also isolated a series of lanthanide-dependent DNAzymes 15, 41-43.…”
Section: Some Representative Dnazymesmentioning
confidence: 99%
See 1 more Smart Citation
“…Many interesting progresses were made by using transition metal ions 7, 11, 35. Many DNAzymes were reported to use Zn 2+ 26, 36, UO 2 2+ 14, Cu 2+ 37, Cd 2+ 29, 38, Hg 2+ 39, and Ag + 40. We also isolated a series of lanthanide-dependent DNAzymes 15, 41-43.…”
Section: Some Representative Dnazymesmentioning
confidence: 99%
“…We reported that the 8-17 is even faster than the 10-23 for cleaving chimeric substrates in the presence of Mg 2+ 25. The 8-17 motif has been repeated selected by several labs using Zn 2+ 26, Mg 2+ 27, 28, Ca 2+ 17, 28, Cd 2+ 29, and other conditions with the best activity observed with Pb 2+ 30. Its recurrence has been attributed to the small size, high tolerance to mutations, and high activity 27.…”
Section: Some Representative Dnazymesmentioning
confidence: 99%
“…6 Therefore, it is not surprising that variants of 17E were selected here. In fact, 17E variants have been isolated 8 from many previous selections using different metal ions, 20,22,[32][33][34] which is attributed to its small size, tolerance to mutation, and high activity. 35,36 Unlike previous selections done in clean buffers, serum contains many other chemicals (e.g.…”
Section: Resultsmentioning
confidence: 99%
“…It was previously reported that with this position being an adenine, the activity is optimal with Cd 2+ , Zn 2+ and Mn 2+ . 34 Figure S4). Earlier studies pointed out that the N12 position plays two crucial roles in 17E.…”
Section: Activity Of 17e Variants In Buffermentioning
confidence: 99%
See 1 more Smart Citation